2023
DOI: 10.33395/sinkron.v8i1.11942
|View full text |Cite
|
Sign up to set email alerts
|

Supervised Learning from Data Mining on Process Data Loggers on Micro-Controllers

Abstract: In processing data science, data is needed as input. Sometimes the data needed does not exist in public data, this is where the purpose of this research is made. The acquisition process is so important to process information into data. After that, the data is processed to make a decision. Micro-controller in controlling conditions, such as temperature, and humidity are very common devices, and a lot of research has been done. Sometimes discussing it only shows how to create a series and save it on online platf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In research conducted by (Hidayat, Hendrastuty, & Styawati, 2023) it was found that the a priori method could be used to predict Android-based sales with an average result of 91.64%. Not only methods, this research also uses data mining, which is a data mining system that will change and process data, both numerical and categorical (Abas et al, 2023) (Saputra, Hindarto, & Haryono, 2023). Data Mining can also be used for data classification, this is because data mining methods have various models, such as KNN, Naive Bayes and there are still other methods (Bustomi, Nugraha, Juliane, & Rahayu, 2023) (Aji & Devi, 2023) (S. A.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In research conducted by (Hidayat, Hendrastuty, & Styawati, 2023) it was found that the a priori method could be used to predict Android-based sales with an average result of 91.64%. Not only methods, this research also uses data mining, which is a data mining system that will change and process data, both numerical and categorical (Abas et al, 2023) (Saputra, Hindarto, & Haryono, 2023). Data Mining can also be used for data classification, this is because data mining methods have various models, such as KNN, Naive Bayes and there are still other methods (Bustomi, Nugraha, Juliane, & Rahayu, 2023) (Aji & Devi, 2023) (S. A.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Data mining is the process of analyzing large sets of data to discover patterns, trends, and previously unknown information, which can help in decision making (Aji & Devi, 2023) (Bustomi, Nugraha, Juliane, & Rahayu, 2023). This technique is widely used in a variety of industries, including finance, healthcare, retail, and telecommunications, to gain insights that can increase efficiency, identify new market opportunities, or improve marketing strategies (Saputra, Hindarto, & Haryono, 2023) (Abas et al, 2023). Data mining combines methods from statistics, machine learning, and databases to extract useful information from large and complex data sets (Sinaga, Marpaung, Tarigan, & Tania, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This technique is often used in various industries such as finance, marketing, healthcare, and retail to make more informed and efficient decisions. Data mining combines statistics, predictive analysis, and artificial intelligence technology to process and analyze data from various sources (Bustomi, Nugraha, Juliane, & Rahayu, 2023) (Saputra, Hindarto, & Haryono, 2023). This process involves several main steps, including data collection, data cleaning, data transformation, data mining, evaluation, and application of results (Abas et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%